The things we carry : strategies for recognizing and negotiating emotional labor in writing program administration - Wooten, Courtney Adams; Babb, Jacob; Costello, Kristi Murray; Navickas, Kate (Utah State University Press, 2020)
"Emotional labor is not adequately discussed by writing program administrators. The Things we carry makes this often-invisible labor visible, demonstrates a strategy to navigate it reflectively, and opens a path for research. This collection considers how writing program administrators work when their schools or regions experience crisis situations"--Provided by publisher--